(untitled) (Eurasian Medical Research Periodical, 2022)
Laryngeal mask - is a medical device that keeps the patient’s airway open during anaesthesia or loss of consciousness. It is a type of supraglotic airway device. Purpose know role of General Anaesthesia in supraglottic airway device by using Hemodynamic Response Method 30 patients were collected for this study from different Hospitals in Iraq. and patients were divided into two groups: the laryngeal mask airway, which included 15 patients, and the ET group, which included 15 patients. Results and conclusion By using the statistical analysis program SPSS SOFT 22, the real value and the arithmetic mean of the ages of patients in the LMA group was 33.4 ± 6.06 and as for the ages of the second group ET 32.2 ± 5.6 Not elevated rates were obtained in LMA in contrast to the levels in the ET group, and statistically significant differences of less than, or equal to 0.001 were found, which indicates that the laryngeal mask is an effective means of securing a clean airway during elective surgeries